2014
DOI: 10.1007/s12031-014-0313-8
|View full text |Cite
|
Sign up to set email alerts
|

Poloxamer-188 Can Attenuate Blood–Brain Barrier Damage to Exert Neuroprotective Effect in Mice Intracerebral Hemorrhage Model

Abstract: Blood-brain barrier (BBB) disruption and brain edema formation play important roles in the secondary neuronal death and neurological dysfunction induced by intracerebral hemorrhage (ICH). Poloxamer 188 (P188), a multiblock copolymer surfactant, has been shown to be capable of sealing damaged cell membranes and decrease neuronal cell death. In this study, we explored whether P188 had a protective effect against ICH and its underlying mechanisms. Male ICR mice were subjected to infusion of type IV collagenase (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…We also observed reduction in MA-mediate apoptosis as a result of p65 silencing, which consolidates the role of NF-κB in MA-mediated toxicity. Since NF-κB activation leads to increase in pro-inflammatory cytokine/chemokines [15], cytotoxicity in brain microvascular endothelial cells via redox imbalance [79] and induce BBB dysfunction [80, 81], it is evident that it plays a multi-factorial role in MA-mediated cytotoxicity. The results presented in this study further supports the notion that MA employs several mechanisms that converge to NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed reduction in MA-mediate apoptosis as a result of p65 silencing, which consolidates the role of NF-κB in MA-mediated toxicity. Since NF-κB activation leads to increase in pro-inflammatory cytokine/chemokines [15], cytotoxicity in brain microvascular endothelial cells via redox imbalance [79] and induce BBB dysfunction [80, 81], it is evident that it plays a multi-factorial role in MA-mediated cytotoxicity. The results presented in this study further supports the notion that MA employs several mechanisms that converge to NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the effect of P188 in autophagy following TBI both in vitro and in vivo, in which autophagy was activated subsequent to P188 treatment. P188 can be directly embedded in the cell membrane lipid layer in vitro and restore plasma membrane integrity in multiple cells [8,16]. Recent studies have shown that autophagy is increased after TBI [4].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) typically contributes to the disintegrity of cell membrane and threatens neuronal survival [9,18]. However, poloxamer 188 (P188) is an amphiphilic polyethylene-polypropylene-polyethylene copolymer, characterized by its properties in sealing membranes and restoring the plasma membrane integrity of neurons following membrane injury [8,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…The rats were deeply anesthetized with 10% chloral hydrate (3-5 mL/kg intraperitoneally) and decapitated. The brain water content was measured using a drying method [10]. With the cerebellar tissue removed, the wet weight of the right and left hemispheres was measured.…”
Section: Measurement Of Brain Water Contentmentioning
confidence: 99%